Profitabilitas Skala: Analisis Komparatif Kinerja Keuangan Usaha Kost - Iman Putra Jaya Ndraha; Krisnawati Setyaningrum Nugraheni (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The boarding house business is a rapidly growing residential rental property sector but has received minimal research from its financial management aspect. This study analyzes the financial performance of three boarding house business models in the Bawen-Ambarawa area using descriptive analysis and financial ratio calculations (NPM, OER, ROI). Data were collected through observation, interviews, and documentation of monthly financial reports for three months. The analysis shows a "Profitability of Scale" divided into two: the large-scale San Boarding House (33 rooms) with premium prices achieved the highest absolute profit and superior ROI (22.04%), while the smallest-scale Tri Boarding House (7 rooms) with the lowest price recorded the highest Net Profit Margin (NPM) (68.14%) due to extreme cost efficiency. These findings confirm that cost management efficiency (OER) is a determinant of margin, while the combination of large scale and premium pricing strategies determines profit volume and total return on investment.